Vatroslav Jagić - A Short Account of His Life and Work - Karlić, Virna (Array, 2014)
Vatroslav Jagić is one of the greatest and most productive Slavists of all times, whose numerous philological contributions in various fields represent the foundations of Slavic philology and to this day define the further development of the field. Since he had very broad interests and was a prolific author, an account of Jagić’s contributions is not an easy task. The first part of the paper provides a brief biography ; the second part describes the scope of his work, most significant works and most notable contributions he left behind, and aims at drawing attention to the substantial role he played in the development of Slavic philology. The final part explores Jagić’s scientific contributions and his impact from a present-day perspective.